Bentuk Partisipasi Masyarakat Dalam Implementasi Program (KOTAKU) Kota Tanpa Kumuh - Saadah Lutfiah; Dindin Solahudin (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
This study aims to determine participation, strategies to increase participation and to determine the results of raising participation. The research method used is descriptive method, with the type of qualitative research data. Based on the results of the research, it can be concluded that: community participation in implementing the KOTAKU program has been quite successful, in this case it can be seen based on community involvement in every stage of the program such as making decisions, being involved in the implementation of development by donating labor, materials and the like, and the community being involved in evaluating the results of program implementation.BKM-MS uses a strategy with a partnership pattern to improve the quality of the environment so that it creates a sense of responsibility and a desire to protect the environment, provides opportunities for the community to participate.